Blockchain enabled smart community for bilateral energy transaction. (June 2023) - Wang, Xiaodi; Liu, Youbo; Ma, Ruiguang; Su, Yunche; Ma, Tiannan
Highlights: A Hyperledger Fabric blockchain embedded community market framework is established. Fine-grained access control and clearly defined authority membership for energy trading services is designed. A near-real-time bilateral trading structure is proposed with energy balance mechanism for real-time imbalance power managing. Fine-grained access control and clearly defined authority membership for energy trading services is designed. The benchmark is presented to evaluate the system performance metrics. Abstract: The blockchain enabled near-real-time, peer-to-peer energy trading market is one of the promising ways to enhance energy system flexibility, achieve peer privacy preserving and transaction trackability. However, providing blockchain-based solutions compatible with energy trading is not an easy task, where real-world feasibility for business model, blockchain configuration, and physic limitations is rather to be investigated. In this work, a permissioned Hyperledger Fabric (HF) blockchain is leveraged to implement real-world applications for energy trading in a smart community. A near-real-time bilateral trading scheme, directly negotiated on a peer-to-peer basis without any intermediary, is designed for achieving supply–demand balance within power network limits. Thenceforward, the specific process of the HF blockchain establishment and the smart contract creation for system initialization, registration, negotiation, trading, balancing and settlement, are detailed demonstrated. In addition, the benchmark is presented to test the performance metrics of execution time, latency, throughput for feasibility and scalability analyses in real-world application. The results illustrate the proposed HF-assisted energy trading platform corroborates the feasibility for the future scalable P2P trading.